A CTA-shuttled R-group approach: a versatile synthetic tool towards well-defined functional cylindrical polymer brushes via RAFT polymerization. Issue 17 (10th April 2017) - Wang, Yifei; Zheng, Zhicheng; Huang, Zhengdong; Ling, Jun
Abstract : We report a novel three-step strategy toward polyCTA for the synthesis of cylindrical polymer brushes via "CTA-shuttled" RAFT R-approach polymerization. Post functionalizations on the CTA residue are also discussed. Abstract : We report a new synthetic route of a polymer backbone (polyCTA) containing chain transfer agent (CTA) pendent groups with a theoretical degree of polymerization (DP) up to 1200 and narrow polydispersity through reversible addition–fragmentation chain transfer (RAFT) polymerization of 4-vinylbenzyl acetate (VBA) followed by three modification steps. Well-defined cylindrical polymer brushes (CPBs) with polystyrene side chains are synthesized from the polyCTA via "CTA-shuttled" RAFT polymerization to prove the feasibility. Furthermore, various post-functionalizations on CPBs are investigated to demonstrate the potential of building complex architectures. CPBs with polystyrene- b -poly( N -isopropylacrylamide) side chains, amine-terminated polystyrene side chains and polystyrene- b -poly(ethylene glycol) side chains are synthesized successfully by the direct chain extension of N -isopropylacrylamide, one-pot aminolysis and Michael addition using acrylates containing a tert -butoxy carbonyl (Boc) protected amine group or mono-methyl poly(ethylene glycol), respectively. The strategy of "CTA-shuttled" R-group approach RAFT polymerization along with post-functionalization exhibits versatility in preparing tailor-made CPBs.